The Ideology of the Unspectacular: Theatricality and Charles Lamb’s Essayistic Figure - Hull, Simon (Romanticism on the Net, 2007)
AbstractThe OED defines “theatricality” in essentially negative terms, as the degraded cultural progeny of the theatre itself, and in the process associates it with spectacle. Assuming cultic proportions in late-Regency London, theatricality, I argue, comes full circle to engulf theatre itself. Epitomized by the mesmeric Kean and an increasing reliance on spectacular effects, this is the point at which Lamb enters the argument. A combined study of theatrical culture and periodical writing in the Romantic period, I demonstrate how such a spectacularization of theatre informs Lamb’s performance with Elia of an “essayistic figure”.Through Elia’s ludic, phantasmal ontology in the London Magazine - in which the illusion of autobiography is enacted and the essay form transcended with assertions of fictive liberty - Lamb’s use of a persona is, like theatricality itself, derivative of theatre. Yet the frequent readjustment of expectations that Elia’s playfulness demands of the reader clearly designates Lamb’s as a readerly mode of theatricality that diametrically opposes the dominant model of ritualistic spectatorship.Indeed, Lamb’s career seemingly embodies the Romantic ambivalence over theatre identified by Mary Jacobus. Both failed playwright and avid theatre-goer, Lamb famously priveliges the reader’s over the audience’s experience of Shakesperare’s tragedies, then later - as Elia - celebrates artificial comedy for the escape it affords from the “diocese of strict conscience”. Elia can perhaps, therefore, be read as Lamb’s attempt at managing theatre on his own terms: an appropriation of its illusory, emancipative qualities to the unspectacular format of the familiar essay.